Experimental investigation on flue gas condensation heat recovery system integrated with heat pump and spray heat exchanger - Zhang, Qunli; Liu, Tao; Cheng, Xuanrui; Guo, Shuaifei; Zhang, Lin; Lü, Xiaoshu (Elsevier, 2024)
To deeply recover the flue gas condensation heat, a flue gas condensation heat recovery system that combines a compression heat pump (FGCHR-HP) is proposed. An experimental bench of the FGCHR-HP system was established to explore the thermal properties of the system under variable operating conditions. The experimental results show that when the inlet water temperature of the heat pump condensing heat exchanger is 50 °C and the flow rate is 40 L/min, the optimal experimental conditions are achieved. Under this working condition, the heat efficiency is 13.8 %, and the exhaust gas temperature is 26.9 °C. At the same time, the flue gas moisture recovery is up to 6.5–7.0 kg/hour, which is better than other boilers.The payback period of the FGCHR-HP system is 3.4 years. The system has achieved significant energy-saving and water-saving effects, and has certain promotion and application prospects.
Keywords: Flue gas heat recovery; Gas boiler; Heat pump; Spray tower; fi=Energiatekniikka|en=Energy Technology|